(untitled) (Bangladesh Journal of Neuroscience, 2014)
Background: The cerebellopontine angle is a space defined by the pyramid anterolaterally, the tentorium superiorly, the pons medially and cerebellum dorsomedially. It is difficult to approach for its complication and vital structures. Objective: To see the outcome of surgery of cerebellopontine angle tumors at the Bangabandhu Sheikh Mujib Medical University. Results: Among the 24 patients 16(66.66%) were males. It was evident that 14(58.33%) belonged to the age group 41-60 years. It was documented that the majority 19(79.16%) of patients had vestibular schwannoma. Among the clinical signs and symptoms the highest group had hearing loss 20(80%). Among 24 patients the tumor was removed completely in 15(62.50%). Among the post operative complications 4(16.66%) developed facial palsy. 2(8.33%) of patients had lower cranial nerve palsy. After operation 1(4.16%) patient died due to aspiration pneumonia. Conclusion: Cerebellopontine angle tumor surgery is a very difficulty operation. But at a tertiary hospital, with help of microscope, we can remove the tumor completely. Bangladesh Journal of Neuroscience 2014; Vol. 30 (2): 90-95